School dropout, lag and repetition: strategies for inclusive and sustainable education in the framework of public policies - Montoliú, Miguel Ángel Esbrí; González, Rosa Elena Durán; Alfaro–Ponce, Berenice; Morales–Maure, Luisa; García-Marimón, Orlando (Edelweiss Applied Science and Technology, 2024)
This study examines the structural factors that contribute to school lag and dropout in students from vulnerable areas. Factors include community violence, economic precariousness, and complex family dynamics, within the context of the post-pandemic impact. Through interviews, participatory observation, and documentary analysis, the experiences of students, teachers, and educational authorities are collected to identify patterns of exclusion. The results show that the socioeconomic context that affects students' motivation, attendance, and school performance, especially in areas with gang presence, is a lack of safe transportation, and poor access to basic services. The pandemic amplified these difficulties by affecting skills such as reading, writing, and math, generating a significant lag as well as an emotional disconnection from school. Although the Ministry of Education implements welfare programs, such as subsidies for food and transportation, their effectiveness is limited in the face of the magnitude of the needs, which generates dissatisfaction in the community. In response, alternative modalities have been explored, such as homeschooling and playful learning programs, as well as interventions in mathematics education that seek to strengthen basic and practical skills, although their impact is still uncertain. This study highlights the need for educational public policies that address the structural causes of dropout and offer early intervention strategies, safe school environments, and teaching methods that connect theory with practice, promoting quality education for all.